Aid Volatility and Macro Risks in Low-Income Countries - Borensztein, Eduardo (OECD Development Centre Working Papers, 2008)
The report argues that aid volatility is an important source of volatility for the poorest countries. Following a method already applied by the Agence Française de Développement, the report argues that loans to LICs should incorporate a floating grace period, which the country could draw upon when hit by a shock. The definition of a shock should include aid uncertainty, along with others such as commodity shocks and natural disasters. The idea is calibrated to a key IMF policy instrument towards Low-Income Countries, the Poverty-Reducing and Growth Facility (PRGF)